2018
DOI: 10.32534/jike.v1i2.156
|View full text |Cite
|
Sign up to set email alerts
|

Whatsapp Messenger as a Mobile Media to Learn Writing for EFL Students

Abstract: Abstract   The objective of this research is to find out the use of Whatsapp Messenger as a mobile media to learn writing in EFL classes.Several researchers have attempted to prove applicability of mobile learning as modern ways of teaching and learning (Naismith, 2004:115). Moreover, applying portable technologies have been demanded by most of the modern learners who oftentimes are forced to study anywhere, and anytime, for example, at work, in the bus or at weekends (Evans, 2008:115).The research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
2
5
0
1
Order By: Relevance
“…These findings were in line with a study conducted by Wahyuni and Febianti (2019) who revealed that the use of WhatsApp group have a potential not only in improving students' writing achievement, but also in facilitating cooperation, increasing social interaction, interest and motivation, sense of belonging, academic success, student-student and student-teacher interaction, and supporting anytime and anywhere learning, providing peer support, feedback, and allowing for information sharing in education. This result is also in line with a study conducted by Linda and Riaeni (2018) who stated that learning using WhatsApp groups is effective to develop their creativity in writing skill. The result showed that most of the students agreed that the teacher facilitated them with good explanations and always provided quick feedback in consultation during online class through WhatsApp.…”
Section: Students' Interaction During Online Class Through Whatsappsupporting
confidence: 91%
“…These findings were in line with a study conducted by Wahyuni and Febianti (2019) who revealed that the use of WhatsApp group have a potential not only in improving students' writing achievement, but also in facilitating cooperation, increasing social interaction, interest and motivation, sense of belonging, academic success, student-student and student-teacher interaction, and supporting anytime and anywhere learning, providing peer support, feedback, and allowing for information sharing in education. This result is also in line with a study conducted by Linda and Riaeni (2018) who stated that learning using WhatsApp groups is effective to develop their creativity in writing skill. The result showed that most of the students agreed that the teacher facilitated them with good explanations and always provided quick feedback in consultation during online class through WhatsApp.…”
Section: Students' Interaction During Online Class Through Whatsappsupporting
confidence: 91%
“…They just need to type and revise their draft in WhatsApp group chat after that re-send it to the WhatsApp group. This finding supports the previous research which was conducted which conducted by (Linda & Ri'aeni, 2018). The result showed WhatsApp Messenger attracts the students interest and also the students have positive responses towards the use of WhatsApp Messenger.…”
Section: Students' Perception Of the Implementation Of Blended Learni...supporting
confidence: 89%
“…In addition, WhatsApp is a very helpful medium to improve communication with supervisors, students state that they can remove the fear of consulting with supervisors. Another study by Linda & Ri'aeni (2018). The difference between this study from the first study is that this study focused on the use of WhatsApp in teaching writing skills.…”
Section: Introductionmentioning
confidence: 92%